US-Australia-Indonesia Trilateral Security? Conditions for Cooperation. Issue 3 (4th May 2019) - Kelton, Maryanne; Willis, David
ABSTRACT: Since the 1950s, US strategic architecture in the Indo-Pacific has been premised on its hubs-and-spokes model of bilateral alliances and security partnerships. Since the 2000s the US began working toward forging deeper interrelationships between its regional allies and partners. The emerging strategy ultimately aims to interlink long-standing allies like Japan and Australia, and also non-traditional partners in the development of a security network capable of maintaining the regional 'rules-based order.' In analysing the US-led triangular Indo-Pacific geometry, this article considers the prospects of an evolving and substantive US–Australia–Indonesia security trilateral. It does so by utilising Miller's 'conditions for cooperation framework' to test the likelihood of greater cooperation between these three states. These conditions include cultural similarity, economic equality, habits of international association, the perception of common danger, and greater power pressure. It concludes that while there remain strict limitations on any formal alignment between the ANZUS partners and Indonesia, there are convergent interests in key sub-strategic areas in the maritime space and thus a viable path toward greater trilateral cooperation but not, as yet, formal arrangements.